Effect of lemon on saliva and Staphylococcus aureus - Batubara, Natasya Angelyna; Lindawati, Yumi (Padjadjaran Journal of Dentistry, 2019)
Introduction: Lemon juice contains citric acid. It is a highly antibacterial organic acid by gargling with, will be able to decrease the spreading of Staphylococcus aureus colony in saliva. The acid stimulation of lemon juice able to increase salivary secretion. The purpose of this study was to see the effect of gargling lemon juice of 100%, 50%, 25%, and 12.5% concentrations towards the salivary flow rate, salivary pH, the number of Staphylococcus aureus colony, and also, correlation between salivary flow rate and pH, salivary flow rate and number of Staphylococcus aureus colony, and salivary pH and number of Staphylococcus aureus colony. Methods: This research conducted with a pre-and-post-test group design. Saliva was taken from 24 subjects before and after the subjects gargled with lemon juice. Measurements performed were salivary flow rate per minute, and salivary pH (using pH Hanna Instrument). The Staphylococcus aureus bacteria were placed in a Mannitol Salt Agar for 24 hours at 370C temperature, then the number of the colonies were counted (x103 CFU). Results: The Wilcoxon test results showed that lemon juice with 100%, 50%, 25%, and 12.5% concentrations significantly increased the salivary flow rate and decreased the number of Staphylococcus aureus colony (p < 0.05). The result of the paired t-test showed that lemon juice with 25% and 12.5% concentration decreased the salivary pH significantly (p<0,05). The Pearson’s correlation results showed no significant correlation between salivary flow rate and salivary pH, flow rate and the number of Staphylococcus aureus colony, and salivary pH and number of Staphylococcus aureus colony. Conclusion: Lemon juice can decrease the salivary pH and the number of Staphylococcus aureus colony, but increases the salivary flow rate. It is considered to be good enough as one of the ingredients of mouthwash.Keywords: Flow rate, lemon, pH, saliva, Staphylococcus aureus